Pengaruh Emotional Quotient, Intelectual Quotient And Spiritual Quotient Terhadap Kinerja Karyawan - Mutaqiyatun, Ani (Jurnal Manajemen Bisnis, 2010)
This reaserch was aimed to analyzing the effect of emotional, intllectual and spiritual quotient upon administrative employee performance at Ahmad Dahlan University located in Jogjakarta. Multiple regression analysis was applied in the research. F test was employed to excamine the effect of all independent variabels upon adminstrative employee performance, and t-test was employed to excame the partial effect.The result show that the administrative employee perpormance significantly affected by emotional,intellectual and spiritual quotient, both together and partial. But spiritual quotient give more contribution influence to administrative employee performance than emotional quetient. Base on the result, emotional, intellectual and spiritual quetient also very significantly influence in case to increase administrative employee optimum performance until 48% (R Square =0,48). The rest 52% was couse by other variables from outside theis reserch like: institutional policy, institutional facility etc.